2000
DOI: 10.1021/ja992886g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Simulation of Biogenesis of the 2,4,5-Trihydroxyphenylalanine Quinone Cofactor of Copper Amine Oxidases:  Mechanistic Distinctions Point toward a Unique Role of the Active Site in the o-Quinone Water Addition Step

Abstract: The biogenesis of the 2,4,5-trihydroxyphenylalanine quinone (TPQ) cofactor from tyrosine at the active site of copper amine oxidases is believed to proceed along a pathway that includes a conjugate addition of water to the corresponding o-quinone intermediate, followed by autoxidation of the resulting benzenetriol to the hydroxyquinone cofactor. The water addition reaction has been presumed to occur not only in previous model studies reported for cofactor biogenesis starting with either catechol or o-quinone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 36 publications
1
39
0
1
Order By: Relevance
“…Furthermore, this is the first study to indicate that a very strong neurotoxic agent like TOPA [60][61][62][63][64] could be formed from non-enzymatic oxidation of a biological substrate such as tyrosine by copper MCO. The shift in the retention time of HPLC results as shown in Table 3(a) could result from the formation of o-Topaquinone (2,4,5-trihydroxyphenylalanine quinone) from TOPA [65].…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, this is the first study to indicate that a very strong neurotoxic agent like TOPA [60][61][62][63][64] could be formed from non-enzymatic oxidation of a biological substrate such as tyrosine by copper MCO. The shift in the retention time of HPLC results as shown in Table 3(a) could result from the formation of o-Topaquinone (2,4,5-trihydroxyphenylalanine quinone) from TOPA [65].…”
Section: Discussionmentioning
confidence: 84%
“…By analogy with the mechanism in Scheme , this was taken to show that the active nucleophile in this reaction is a free, rather than Cu‐bound, hydroxide ion 32. However, it has recently been demonstrated that, under these conditions, the O atom at the C‐2 position is, in fact, derived by conjugate addition of H 2 O 2 , which is produced as a by‐product of catechol oxidation (Scheme ) 34. The preference for nucleophilic attack of HO 2 − rather than OH − in vitro can be attributed to the lower p K a of H 2 O 2 compared to H 2 O.…”
Section: Methodsmentioning
confidence: 95%
“…Analysis of the isotopic pattern with Isotopica47 indicates that these patterns result from incorporation of between 0.3 and 0.5 18 O atoms. This analysis is only possible with MALDI‐TOFMS as the carbonyl 18 O will back‐exchange during LC/MS 48, 49. The observation of a single substoichiometric 18 O exchange may prove useful for the identification of protein modifications containing solvent‐exchangeable carbonyl groups even when the mass change of this modification is not known.…”
Section: Resultsmentioning
confidence: 99%